Real-world efficacy and safety of mobocertinib in EGFR exon 20 insertion-mutated lung cancer - Kian, Waleed; Christopoulos, Petros; Remilah, Areen A.; Levison, Esther; Dudnik, Elizabeth; Shalata, Walid; Krayim, Bilal; Marei, Ranin; Yakobson, Alexander; Faehling, Martin; Kahala, Dolev; Sara Granot, Inbal; et al. (Frontiers in Oncology, 2022)
Background: Non-small cell lung cancer (NSCLC) harboring EGFR exon 20 insertions (EGFRex20ins) is relatively resistant to the existing EGFR tyrosine kinase inhibitors (TKIs). Mobocertinib is a novel TKI that selectively targets EGFRex20ins and has demonstrated therapeutic efficacy in pretreated patients with tumors harboring these mutations. Methods: This is a retrospective, non-interventional, multicenter real-world study aimed at assessing the efficacy and safety of mobocertinib in patients with EGFRexon20ins who received 160 mg QD monotherapy as part of expanded access. Data collection was based on patients’ records. PET-CT or CT scans were used to measure systemic response, while brain MRIs were used to examine intracranial response as part of the follow-up. Results: 16 patients were included in this report. Mobocertinib was administered to 31.3% (5) of patients as first-line, 50% (8) as second-line, and 18.7% (3) as a later-line therapy. The median age was 65 years (range, 38-83), 75% (12/16) were female, and 50% (8/16) had brain metastases at baseline before mobocertinib treatment. The objective response rate (ORR) to mobocertinib was 25% (4/16) (1/5 for first line and 3/11 for other lines), disease control rate (DCR) was 75% (12/16) with a follow-up period of 11 months. The median duration of treatment (mDoT) was 5.6 months across all patients, and 8.6 months in responders. Based on the presence or absence of brain metastasis, the mDoT was 14.8 and 5.4 months (p=0.01), respectively. Mobocertinib Grade ≥3 treatment-related adverse events (TRAEs) included diarrhea (19%), nausea (6%) and renal failure (6%). Dose reduction was reported in 25% of cases to 80 mg. Conclusion: Mobocertinib in compassionate use exhibited an ORR of 25%, which is very similar to that of the phase 2 EXCLAIM study and clearly better than historical data of monochemotherapy or conventional EGFR inhibitors. The greatest benefit was noted in patients without brain metastases, who showed durable effects with mDoT 14.8 months, while intracranial activity was limited. These findings may assist therapeutic considerations, inasmuch as results from the EXCLAIM cohort-3 dedicated to brain lesions are not available yet.